Family and school adaptation of the adopted child - Ocón Domingo, José; Álvarez Rodríguez, José (Profesorado, Revista de Currículum y Formación del Profesorado, 2011)
This article resumes the actual situation of adoption in Spain and the contributions by the Spanish researching. But it mainly includes an unpublished researching about the adoption in Andalusia, considering the dynamics of seven adoptive families: four national and three international. The selected results are mainly focused on upheavals suffered by adopted child concerning the following questions: health, personal development, affective-behaviour and school. In order to understand all these approaches a new qualitative methodology has been adopted on the basis of an open interviewing process to adoptive parents.